2020
DOI: 10.1186/s12944-020-01398-1
|View full text |Cite
|
Sign up to set email alerts
|

Early postpartum dyslipidemia and its potential predictors during pregnancy in women with a history of gestational diabetes mellitus

Abstract: Background This study aimed to analyze the incidence of early postpartum dyslipidemia and its potential predictors in women with a history of gestational diabetes mellitus (GDM). Methods This was a retrospective study. Five hundred eighty-nine women diagnosed with GDM were enrolled and followed up at 6–12 weeks after delivery. A 75 g oral glucose tolerance test (OGTT) and lipid levels were performed during mid-trimester and the early… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…The HbA1c cutoff for a high risk profile for postpartum dyslipidemia in normoglycemic women with pGD in our study was almost in agreement with previous findings [4]. According to our results, even in conditions where glycemic goals (FPG and HbA1c) are achieved, women with GD might be at risk for postpartum dyslipidemia after delivery, even when they are normoglycemic [4]. On the other hand, lipid parameters during mid-pregnancy should not be ignored due to a lack of therapeutic importance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The HbA1c cutoff for a high risk profile for postpartum dyslipidemia in normoglycemic women with pGD in our study was almost in agreement with previous findings [4]. According to our results, even in conditions where glycemic goals (FPG and HbA1c) are achieved, women with GD might be at risk for postpartum dyslipidemia after delivery, even when they are normoglycemic [4]. On the other hand, lipid parameters during mid-pregnancy should not be ignored due to a lack of therapeutic importance.…”
Section: Discussionsupporting
confidence: 93%
“…Simultaneously, it has been shown that age, weight, and lipid status during pregnancy are associated with the risk of postpartum dyslipidemia [4][5][6]. On the other hand, dyslipidemia during pregnancy is a common physiological phenomenon, especially after mid-trimester, since increased levels of lipids are essential for fetus development [7].…”
Section: Introductionmentioning
confidence: 99%
“…Existing data on risk factors of T2D among women with a history of GDM were firstly reported in the NHW population, such as greater pre-pregnancy BMI ( 8 , 9 ), excessive weight gain ( 3 ), unhealthy dietary patterns ( 3 ), physical inactivity ( 3 ), and a short period of lactation ( 3 , 10 ). In the Asian population, there are also quite a few at-risk pre-natal maternal characteristics recently added to this pond of evidence, such as family history of diabetes ( 43 ), a higher degree of consanguineous marraiges ( 43 ), higher pre-pregnancy BMI ( 29 , 31 , 32 , 46 ), higher total cholesterol quartile at GDM diagnosis during the index pregnancy ( 47 ), younger age at delivery (<30 years) ( 46 ), and a short period of lactation (<6 months) ( 33 ). Post-natal risk such as missing medical assistance in the continuum of GDM care after delivery could be another risk for T2D progression among Asian mothers with a history of GDM ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Asia, five studies reported metabolic syndrome in Asian women with a history of GDM, with an incidence rate ranging from 40 to 90 per 1000 person-years. One Chinese study reported postpartum dyslipidemia (38.5%) among women with a history of GDM ( 47 ), while the other Israelite study reported a 30-70% higher risk of developing CV events and CV hospitalization among women with a history of GDM, even after adjusting for pre-eclampsia and maternal obesity at index pregnance ( 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…In women with a history of GDM, LDL cholesterol levels >3.56 mmol/L in the second trimester were associated with increased risk of dyslipidaemia at 6–12 weeks post‐delivery. 41 Darmady and Postle found cholesterol levels remained elevated up to 36 weeks post‐partum. 39 The degree of change experienced may also influence associations with outcomes.…”
Section: Discussionmentioning
confidence: 96%